Otoritas Hula-Hula dan Teologi Berkat: Tinjauan Dogmatis Tentang Relasi dan Karunia Allah dalam Konteks Budaya Batak Toba - Boby Andika Sinaga; Henri Naibaho (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This study examines the role of the hula-hula authority within the Batak Toba kinship system, known as Dalihan na tolu, and its relevance to the theological understanding of blessings. In Batak tradition, hula-hula is viewed as "Debata na tarida" (the visible God) and is considered a source of blessings in various social and ritual contexts, especially through the practice of giving ulos. However, Christian doctrinal theology asserts that blessings are solely a gift from God, independent of any specific social structure or tradition. Using a qualitative research method through literature study, this paper explores the intersection and tension between Batak customs and Christian theology. The findings show that while the authority of hula-hula enriches the values of social harmony and kinship ethics, this understanding risks overshadowing the biblical truth that God is the sole source of blessings. Therefore, the church is called to reaffirm God's authority while also respecting cultural values. This study highlights the tension between tradition and theology, which should be addressed with wisdom to allow both to coexist harmoniously.